O grupo escolar de São Luiz do Paraitinga: contexto histórico (décadas de 1930 a 1970) - Pinto, Marina de Campos Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The present work has as its theme the group of St. Louis School of Paraitinga: historical context (the 1930 to 1970). This work has the distinction the subject rarely addressed in academic, school groups in the region of Vale do Paraiba, these schools are not constant theme of research, making this differentiation materials present little used, but extremely important for understanding of education present in the region of Vale do Paraíba. For the realization was made to read the legislation in the period 1930 to 1970, the documentation provided by the Department of Education, reading and analysis of documentation presented, one can understand the historical context of the school group to be targeted by the study: School Group Colonel Domingues de Castro. Objective of this study was to understand how the group of the school of St. Louis was shaping up Paraitinga laws and guidelines in the historical context of the decades from 1930 to 1970, contextualizing historical events general and the specific events of São Luiz do Paraitinga. The methodology used is studies of educational phenomena along with the narrative-biographical study of respondents to this survey

O presente trabalho tem como tema O grupo escolar de São Luiz do Paraitinga: contexto histórico (décadas de 1930 a 1970). Este trabalho tem como diferencial a temática pouco abordada na área acadêmica, os grupos escolares da região do Vale do Paraíba, estas escolas não são tema constante de pesquisa, fazendo com que essa diferenciação apresente materiais pouco utilizados, porém de extrema importância para compreensão da educação atual na região do Vale do Paraíba. Para a realização foi feita a leitura da legislação vigente no período de 1930 a 1970, a documentação disponibilizada pela Secretaria da Educação, a leitura e análise das documentações apresentadas, pode-se entender o contexto histórico do grupo escolar que será alvo do estudo: o Grupo Escolar Coronel Domingues de Castro. Foi objetivo desse trabalho compreender como o grupo escolar de São Luiz do Paraitinga foi se moldando às leis e diretrizes no contexto histórico das décadas de 1930 a 1970, contextualizando os acontecimentos históricos gerais e os acontecimentos específicos da cidade de São Luiz do Paraitinga. A metodologia usada será estudos de fenômenos educacionais juntamente com a pesquisa narrativo-biográfica dos entrevistados por esta pesquisa
Keywords: Escolas; Educação - Historia; Escolas - Normas; Schools; Comparative education; Standards